2002
DOI: 10.1002/bit.10297
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation strategies for improved heterologous expression of laccase in Pichia pastoris

Abstract: Improved expression of recombinant laccase by Pichia pastoris carrying the lcc1 cDNA isolated from Trametes versicolor was achieved by optimization of the cultivation conditions in a fermentor equipped with a methanol sensor system. The results indicated that the activity obtained in fermentor cultivations was at least 7 times higher than in shake-flask cultures. Three different strategies for fermentor cultivations were compared: A (30 degrees C, 1.0% methanol), B (20 degrees C, 1.0% methanol), and C (20 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
107
0
10

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(133 citation statements)
references
References 46 publications
16
107
0
10
Order By: Relevance
“…anol or intermediates formed during methanol catabolism (29,41,46). The observation that cells which had previously been exposed to (and simultaneously utilized) methanol are more sensitive to any additional stress factor introduced subsequently is consistent with previous results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…anol or intermediates formed during methanol catabolism (29,41,46). The observation that cells which had previously been exposed to (and simultaneously utilized) methanol are more sensitive to any additional stress factor introduced subsequently is consistent with previous results.…”
Section: Discussionsupporting
confidence: 90%
“…The optimum pH value for Pichia growth is approximately 5 (6), but the pH value is commonly reduced to counteract proteolysis (9,32) or to increase both the stability and productivity of heterologous proteins (5,29,56). However, a pH value of 4 or lower can compromise cells during the production process (27).…”
mentioning
confidence: 99%
“…Our results support the positive effect of low temperatures (20°C) on laccase production. Low temperatures can benefit protein folding, as they reduce cell growth rates, allowing non-rate-limiting protein folding (27). Although the S. cerevisiae strain used in this work is protease deficient, reduced activity of residual proteases at low temperature cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Lower cultivation temperature can also influence yields of recombinant protein, possibly due to poor stability of the recombinant protein at higher temperatures, release of more proteases from dead cells, and folding problems at higher temperatures [48]. Li and co-workers [64] have shown that lowering the process temperature (from 30 • C to 23 • C) increased the yield of herring antifreeze proteins from 5.3 mg/l to 18.0 mg/l, and also increased cell viability.…”
Section: Cultivation-level Strategiesmentioning
confidence: 99%
“…Li and co-workers [64] have shown that lowering the process temperature (from 30 • C to 23 • C) increased the yield of herring antifreeze proteins from 5.3 mg/l to 18.0 mg/l, and also increased cell viability. Hong et al [48] achieved higher laccase activity by decreasing the cultivation temperature (from 30 • C to 20 • C) and by reducing methanol concentration (from 1.0% to 0.5%). Jahic et al [54] obtained much higher concentration of a fusion protein by applying a temperature-limited fed-batch (TLFB) technique compared with the traditional methanol fed-batch technique.…”
Section: Cultivation-level Strategiesmentioning
confidence: 99%